Selection of Exopolysaccharide-Producing Lactobacillus Plantarum (Lactiplantibacillus Plantarum) Isolated from Algerian Fermented Foods for the Manufacture of Skim-Milk Fermented Products - Bachtarzi, Nadia (Microorganisms, 2020)
The exopolysaccharide (EPS)-producing Lactobacillus plantarum (renamed as Lactiplantibacillus plantarum) LBIO1, LBIO14 and LBIO28 strains, isolated from fermented dairy products typical from Algeria, were characterized to evaluate the impact of the polymers in milk fermentations. Their genomes revealed the presence of two complete eps clusters of the four described for the reference strain WCFS1. Besides, the three strains presented identical sequences of eps3 and eps4 clusters, but LBIO1 and LBIO28 harbour three genes belonging to eps2 which are absent in the LBIO14 genome. The EPS purified from fermented skim-milks manufactured with the strains showed identical nuclear magnetic resonance ((1)H-NMR) and size exclusion chromatography coupled with a multiangle laser light scattering detector (SEC-MALLS) profiles for polymers LBIO1 and LBIO28, whereas LBIO14 EPS was different due to the lack of the high-molecular weight (HMW)-EPS and the absence of specific monosaccharide’s peaks in the anomeric region of its proton NMR spectrum. The presence of the HMW-EPS correlated with optimal sensorial-physical characteristics of the fermented skim-milks (ropy phenotype). Their microstructures, studied by confocal scanning laser microscopy (CSLM), also showed differences in the organization of the casein-network and the distribution of the bacteria inside this matrix. Therefore, the strain LBIO1 can be proposed for the manufacture of dairy products that require high whey retention capability, whereas LBIO28 could be applied to increase the viscosity.